AUGMENTED AND VIRTUAL REALITY IN MEDICINE: THE ANALYSIS OF COMPETITIVE LANDSCAPE - O. V. Cherchenko (Ekonomika Nauki, 2018)
To assess the potential for the development of virtual and augmented reality technologies, as well as the competitiveness of Russian developments, a patent-market analysis of one of the dynamically developing technological areas introduced in the program «Digital Healthcare» was done. The results of the completed patent study allow us to characterize the direction of «virtual and supplemented reality in medicine» as a promising, but far from generating market products and services that could form a new market within 3–5 years. Despite the great interest in digital technologies and the new design of the economy that they created, the Russian Federation still occupies the 11th place in the world for patent activity in the field of virtual and augmented reality in medicine, and obviously underestimating the fact that the first positions of the world companies rating by the volume of patent portfolios are already occupied by such experienced market players as Philips, Sony, Samsung Electronics, Siemens healthcare, General Electric and Microsoft technology licensing.